2020
DOI: 10.1021/acs.orglett.0c03660
|View full text |Cite
|
Sign up to set email alerts
|

NHC-Nickel Catalyzed C–N Bond Cleavage of Mono-protected Anilines for C–C Cross-Coupling

Abstract: A Ni-catalyzed aryl C–N bond cleavage of mono-protected anilines, N-arylsulfonamides, has been developed. A new N-heterocyclic carbene derived from benzoimidazole shows high reactivity for the C–N cleavage/C–C cross-coupling reaction. The ortho-directing group is not required to break the C–N bond of sulfonyl-protected anilines, which are not limited to π-extended anilines. The mechanistic studies have revealed that a sulfamidomagnesium salt is the key coupling intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The first Ni-NHC-catalyzed cross-coupling of aryl CÀ N bond with a Grignard reagent via direct aryl CÀ N bond cleavage was reported by Xia et al [75] The strategy of incorporating electronwithdrawing protecting group, N-trifluoromethylsulfonyl (NÀ Tf) onto the nitrogen of aniline enabled the weakening of aryl CÀ N bond, enhancing the acidity of NH to form amido salt intermediate, solving the challenges of enthalpy barrier and eliminating the possibility of amination. Additionally, the authors found that the aniline substrates did not require ortho directing group and were not limited to π-extended aryl amines.…”
Section: Kumada Couplingmentioning
confidence: 99%
“…The first Ni-NHC-catalyzed cross-coupling of aryl CÀ N bond with a Grignard reagent via direct aryl CÀ N bond cleavage was reported by Xia et al [75] The strategy of incorporating electronwithdrawing protecting group, N-trifluoromethylsulfonyl (NÀ Tf) onto the nitrogen of aniline enabled the weakening of aryl CÀ N bond, enhancing the acidity of NH to form amido salt intermediate, solving the challenges of enthalpy barrier and eliminating the possibility of amination. Additionally, the authors found that the aniline substrates did not require ortho directing group and were not limited to π-extended aryl amines.…”
Section: Kumada Couplingmentioning
confidence: 99%
“…2−6 The C−N bonds of arylpyridinium salts, which are readily prepared from anilines, are also transformed by a photoredox or Lewis base catalyst (Scheme 1, a-1). 7−9 For other methods, nickel-catalyzed reduction and borylation of N-aryl amides 10 and coupling reactions of N-arylsulfonamides 11 and N-aryl amides 12 via C− N bond cleavage were developed (Scheme 1, a-2). In these reactions, the C−N bonds are more reactive than those of the corresponding amino groups because of the electron-withdrawing effect of the acyl or sulfonyl groups.…”
mentioning
confidence: 94%
“…To overcome this problem, several strategies for C–N bond transformation have been developed. Typically, highly reactive species, such as quaternary ammonium salts ([Ar-NR 3 ] + ) and diazonium salts ([Ar-N 2 ] + X – ), are prepared from arylamines in advance or in situ, and their C–N bonds are consequently converted to various functional groups by coupling reactions or radical reactions (Scheme , a-1). The C–N bonds of arylpyridinium salts, which are readily prepared from anilines, are also transformed by a photoredox or Lewis base catalyst (Scheme , a-1). For other methods, nickel-catalyzed reduction and borylation of N -aryl amides and coupling reactions of N -arylsulfonamides and N -aryl amides via C–N bond cleavage were developed (Scheme , a-2). In these reactions, the C–N bonds are more reactive than those of the corresponding amino groups because of the electron-withdrawing effect of the acyl or sulfonyl groups.…”
mentioning
confidence: 99%
“…In the past decades, C–N bond cleavage and transformation of anilines have attracted a great deal of attention and become a promising bond disconnection and formation strategy in organic synthesis . C–N transformation of primary anilines has mainly relied on a preactivation strategy by transforming anilines to activated diazonium, ammonium, and pyridinium salts or reactive (sulfon)­amides . However, because of the high bond dissociation energy, the direct transformation of tertiary and secondary anilines is a huge challenge.…”
mentioning
confidence: 99%